Gormenghast a BBC-Production Based on the Novels by Mervyn Peake - Wilson, Andy; Finney, Gavin; Meyers, Jonathan Rhys; Lee, Christopher; Shaw, Fiona (BBC Worldwide, 2000)
The BBC's lavish, glowingly designed adaptation of Mervyn Peake's eccentrically brilliant novels "Titus Groan" and "Gormenghast" is a triumph of casting ... Wilson and his design team achieve a look rather more pre-Raphaelite than Peake's own illustrations, shabby velvets, garish sunlight and dank stone passages. The score by Richard Rodney Bennett is full of attractive surprises - fanfares and waltzes and apotheoses - and John Tavener's choral additions are plausibly parts of the immemorial ritual of Gormenghast. [www.amazon.co.uk]